Minority Breast Cancer Survivors: The Association between Race/Ethnicity, Objective Sleep Disturbances, and Physical and Psychological Symptoms - Pinky H. Budhrani; Cecile A. Lengacher; Kevin E. Kip; Cindy Tofthagen; Heather Jim (Nursing Research and Practice)
Background. Limited research has been conducted on the moderating effect of race/ethnicity on objective sleep disturbances in breast cancer survivors (BCSs). Objective. To explore racial/ethnic differences in objective sleep disturbances among BCSs and their relationship with self-reported symptoms. Intervention/Methods. Sleep disturbance and symptoms were measured using actigraphy for 72 hours and self-reported questionnaires, respectively, among 79 BCSs. Analysis of covariance, Pearson’s correlation, and multivariate regression were used to analyze data. Results. Sixty (75.9%) participants listed their ethnicity as white, non-Hispanic and 19 (24.1%) as minority. Total sleep time was 395.9 minutes for white BCSs compared to 330.4 minutes for minority BCSs. Significant correlations were seen between sleep onset latency (SOL) and depression, SOL and fatigue, and sleep efficiency (SE) and fatigue among minority BCSs. Among white BCSs, significant correlations were seen between SE and pain and wake after sleep onset (WASO) and pain. The association between depression and SOL and fatigue and SOL appeared to be stronger in minority BCSs than white BCSs. Conclusions. Results indicate that white BCSs slept longer than minority BCSs, and race/ethnicity modified the effect of depression and fatigue on SOL, respectively. Implications for Practice. As part of survivorship care, race/ethnicity should be included as an essential component of comprehensive symptom assessments.